A study on fattening Ethiopian sheep. I. Performance of highland lambs under feed-lot conditions - Galal, E.S.E.; Awgichew, K.; Kebede, B.; Gojam, Y.; O'Donovan, P.B. (1979)
Two trials were performed to study the fattening performance of Ethiopian highland sheep under feed-lot conditions. Three diets were tried; A-20 % hay, B -35% hay and C-50% hay. Trial I had the three diets represented on 84 non-descript highland all-milk-tooth ram lambs, while in Trial II, only, diets A and C were tried on 47 highland Horro ram lambs. The average initial veight was 20.4 kg in Trial II. Average daily gain differed significantly (p